Iri dalam Relasi Sosial - Faturochman, - (Faculty of Psychology, Universitas Gadjah Mada, 2006)
Envy is not a new concept but psychoÂ¬lo-gically has not been studied intensively. As a preliminary study, this research describes five basic data on the meaning, experience, time, subject, and coping of envy among university students. The findings show that respondents met difficulties to define envy, however, they had experiences envy toward friends and relatives. Respondents showed many positive startegies to cope with envy that can reduce the potential problems in their social relations. Keywords: Envy, social relation